Photoprotective Effects of Two New Morin-Schiff Base Derivatives on UVB-Irradiated HaCaT Cells - Sara García-Gil; Azahara Rodríguez-Luna; Javier Ávila-Román; Gabriela Rodríguez-García; Rosa E. del Río; Virginia Motilva; Mario A. Gómez-Hurtado; Elena Talero (Antioxidants, 2024)
Ultraviolet (UV) radiation harms the skin, causing oxidative damage, inflammation, and disruption of the skin’s barrier function. There is considerable interest in identifying new natural ingredients with antioxidant and anti-inflammatory properties to serve as adjuvants in sunscreens. The flavonoid morin (1) can undergo structural modifications to enhance its biological properties. The aim of this study was to synthesize two new morin-Schiff base derivatives, morin oxime (2) and morin semicarbazone (3), comparing their photoprotective effects with that of the parent compound on UVB-exposed HaCaT keratinocytes. The chemical structure of the novel compounds was revealed based on spectroscopic data analysis. Our findings demonstrated that derivatives 2 and 3 enhanced the light absorption capability in the UV–visible (vis) range compared to 1. Tested compounds exhibited a higher scavenger capacity than Trolox. Moreover, pre-treatment with all compounds protected HaCaT cells from UVB-induced cell death. Compound 3 demonstrated the strongest antioxidant effect, reducing reactive oxygen species (ROS) generation and, subsequently, malondialdehyde (MDA) levels. Additionally, compounds 2 and 3 exhibited greater anti-inflammatory effects than compound 1, significantly reducing interleukin (IL)-6 production levels at all tested concentrations. These findings have demonstrated, for the first time, a promising photoprotective activity of two new Schiff base derivatives and suggest their use as natural sunscreen ingredients.